Propuesta de mejora para la obtención de aromáticas de la Casa Fusión Andina (2018)
In the present project a diagnosis of the current process was made in which it was found that the critical stages of the process of obtaining aromatics are: the conditioning and cutting, drying and grinding, because it was observed that they were the stages that most time required to obtain the product. The performance and the problems that were generated in the equipment for the processing of 1 kg of each fruit per month were taken into account. Following that, it was proposed to contemplate changes for these stages. A manual fruit processor was proposed for the preparation and cutting. In the case of agraz, the use of a macerator was proposed. In the drying, the change of furnace was contemplated for a greater capacity of processing with a considerable air flow and finally in the milling the use of a semi-industrial reversible motor blender was considered.